Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances